CHAMOMILE TEA INTERVENTION FOR DYSMENORRHEA: EFFECTS ON PAIN AND ANXIETY - Amanda Gilbrania Putri Afandi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Menstrual cramps frequently affect the reproductive well-being of young females, routinely triggering psychological distress that disrupts their academic focus, routine functioning, and general wellness. To mitigate these dual challenges of physical distress and psychological tension, the therapeutic attributes of Matricaria chamomilla, which naturally alleviates muscle spasms, reduces inflammation, and induces calmness, offer a viable alternative. This investigation sought to evaluate how the administration of this herbal infusion modifies both the severity of menstrual discomfort and psychological distress experienced by young students at SMA Islam Duduk Sampeyan. By employing a pre-experimental approach centered on evaluating a single cohort before and after exposure, the researchers gathered data from 31 participants chosen via targeted criteria. The evaluation of physical discomfort utilized a segmented numerical scale, whereas psychological tension was quantified through a specific clinician-rated clinical framework. The resulting data underwent statistical evaluation via a non-parametric paired variance procedure, applying a threshold where alpha equals 0.05. Initial observations indicated that a substantial portion of the cohort struggled with intermediate levels of both physical discomfort and psychological distress. Following the dietary introduction of the herbal infusion, a shifting trend emerged, with most participants experiencing either complete relief or minimal discomfort alongside diminished psychological tension. The non-parametric statistical analysis confirmed this shift, indicating that the drop in both physical suffering and psychological strain was highly meaningful, with the probability value falling below 0.001. Consequently, utilizing this herbal infusion serves as a practical, accessible, and risk-free non-medicinal strategy suitable for young females seeking to manage menstrual discomfort.